Silver nanoparticles induce reactive oxygen species-mediated cell cycle delay and synergistic cytotoxicity with 3-bromopyruvate in Candida albicans, but not in Saccharomyces cerevisiae - Lee B (Dove Medical Press, 2019)
Bokyoung Lee,1,2 Mi Jin Lee,1 Su Jin Yun,1,2 Kyongmin Kim,1,2 In-Hong Choi,3 Sun Park1,21Department of Microbiology, Ajou University School of Medicine, Suwon, 442-749, Republic of Korea; 2Department of Biomedical Sciences, The Graduate School, Ajou University, Suwon, 442-749, Republic of Korea; 3Department of Microbiology, Institute for Immunology and Immunological Diseases, Yonsei University College of Medicine, Seoul, 120-752, Republic of KoreaBackground: Silver nanoparticles (AgNPs) inhibit the proliferation of various fungi; however, their mechanisms of action remain poorly understood. To better understand the inhibitory mechanisms, we focused on the early events elicited by 5 nm AgNPs in pathogenic Candida albicans and non-pathogenic Saccharomyces cerevisiae.Methods: The effect of 5 nm and 100 nm AgNPs on fungus cell proliferation was analyzed by growth kinetics monitoring and spot assay. We examined cell cycle progression, reactive oxygen species (ROS) production, and cell death using flow cytometry. Glucose uptake was assessed using tritium-labeled 2-deoxyglucose.Results: The growth of both C. albicans and S. cerevisiae was suppressed by treatment with 5 nm AgNPs but not with 100 nm AgNPs. In addition, 5 nm AgNPs induced cell cycle arrest and a reduction in glucose uptake in both fungi after 30 minutes of culture in a dose-dependent manner (P<0.05). However, in C. albicans only, an increase in ROS production was detected after exposure to 5 nm AgNPs. Concordantly, an ROS scavenger blocked the effect of 5 nm AgNPs on the cell cycle and glucose uptake in C. albicans only. Furthermore, the growth-inhibition effect of 5 nm AgNPs was not greater in S. cerevisiae mutant strains deficient in oxidative stress response genes than it was in wild type. Finally, 5 nm AgNPs together with a glycolysis inhibitor, 3-bromopyruvate, synergistically enhanced cell death in C. albicans (P<0.05) but not in S. cerevisiae.Conclusion: AgNPs exhibit antifungal activity in a manner that may or may not be ROS dependent, according to the fungal species. The combination of AgNPs with 3-bromopyruvate may be more useful against infection with C. albicans.Keywords: metal nanoparticles, yeasts, anti-infective agents, antimetabolites